Starting a medical technology venture as a young academic innovator or student entrepreneur - Manbachi, Amir; Walch, Philipp (Annals of biomedical engineering, 2018)
Following the footprints of Bill Gates, Steve Jobs and Mark Zuckerberg, there has been a misconception that students are better off quitting their studies to bring to life their ideas, create jobs and monetize their inventions. Having historically transitioned from manpower to mind power, we live in one of the most rapidly changing times in human history. As a result, academic institutions that are supposed to be pioneers and educators of the next generations have started to realize that they need to adapt to a new system, and change their policies to be more flexible towards patent ownership and commercialization. There is an infrastructure being developed towards students starting their own businesses while continuing with their studies. This paper aims to provide an overview of the existing landscape, the exciting rewards as well as risks awaiting a student entrepreneur, the challenges of the present ecosystem, and questions to consider prior to embarking on such a journey. Various entities influencing the start-up environment are considered, specifically for the medical technology sector. These parties include but are not limited to: scientists, clinicians, investors, academic institutions and governments. A special focus will be set on the seemingly unbridgeable gap between founding a company and a scientific career.